Insights into depolymerization of chitosan using acid hydrolysis, direct photolysis, and photocatalysis: A review - Nurul Amanina A. Suhaimi; Nur Batrisyia Amirul; Alessandra Anne Hasman; Nurulizzatul Ningsheh M. Shahri; Nur Nabaahah Roslan; Harry Lik Hock Lau; Cristina Pei Ying Kong; Eny Kusrini; Anwar Usman (Results in Chemistry)
Chitosan is an important natural biopolymer, having a wide range of pharmaceutical, medical, and biomedical applications due to its biocompatibility, biodegradability, nontoxicity, and ability to absorb bioactive compounds. These specific applications require low molecular weight chitosan (LMWC) due to its better biodegradability, biocompatibility, bioactivity, and solubility in water when compared to as-prepared high molecular weight chitosan (HMWC) obtained from the deacetylation of chitin. The conventional methods to convert HMWCs to LMWCs include acid depolymerization and direct photolysis upon UV light irradiation. The use of highly concentrated acids unexpectedly modifies the functional groups of chitosan and has raised the environmental concerns. A recently proposed eco-friendly and efficient approach is advanced oxidation processes utilizing reactive oxygen species to destabilize the glycosidic linkages, followed by hydrolysis and scission of chitosan polymer chains. This review summarizes physical, chemical, and biological properties of chitosan, and applications of this biopolymer especially in pharmaceutical formulation, medicine, biomedicine, agriculture, and wastewater treatment, and insights into methodology, mechanism, and advantages of depolymerization of chitosan using acid hydrolysis, direct photolysis, and photocatalysis, as well as their challenges and limitations in terms of environmental concerns, chemical structure conservation, controllability, and toxicity. The challenges in scaling up the photocatalytic depolymerization process is also discussed based on recovery, reusability, and regeneration of the photocatalysts along with a use of specific facet and morphology of photocatalysts, nanometer-sized multi-phase photocatalysts, and proper photoreactor design and parameters optimization in the photocatalytic depolymerization of chitosan in the future.